Research Paper on Seven-Eleven (7-Eleven) Store Bankruptcy Case in Indonesia - Chandra, Jessica; Syailendra Putra, Moody Rizqy; Lie, Gunardi (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Retail is a business activity to increase the use-value of goods and services so that they are traded to consumers for personal or household consumption. Indonesian retail is generally known as two, namely traditional retail and modern retail. Traditional retail is retail that sells goods and services that can be consumed which are still traditional, such as markets, grocery stores, and stalls which can be found almost everywhere, while modern retail is the development of traditional retail by implementing newer concepts, such as the use of technology and keep up with the times and even accommodate people's lifestyles. This study uses a qualitative approach, namely identifying previous studies both from scientific articles, books and theories concerned with existing phenomena. This research is focused on the causes of bankruptcy faced by 7-Eleven and how to deal with the risks that occur in 7-Eleven. 7-Eleven officially closed for several reasons, namely business closing quickly and aggressively, swelling financial statements, decreased purchasing power and excess operational costs. Based on the research results that have been obtained, the suggestions that can be conveyed by researchers are to make investments, it is advisable not to invest when financial conditions are unstable. This is suggested based on the results of research calculations and from a financial perspective, companies are advised to look at and pay attention to the proportion of financial reports such as excessive use of funds. And from the company side 7-Eleven also needs to be more assertive towards consumers who use excessive facilities such as limiting the use of the internet and other sources. It is suggested that companies do not experience difficulties in paying debts and for further researchers it is suggested to give more priority or attention to corporate sectors other than trading companies, such as manufacturing, to prove that the Altman Z-Score method can be applied to predict bankruptcy in different types of companies.